A general overview of native courts in Sabah / Amira Razali...[et al.] - Razali, Amira; Sumatra, Jack Danautoba; Abd. Manan, Noor Farihainie; Sulaiman, Siti Nur Syuhadah (Faculty of Law, 2013)
The objective of this research is to strengthen the Native Court of Sabah in Malaysia. There are two Native Courts in Malaysia which are Native Court of Sabah and Sarawak. But this research will focus on the Native Court of Sabah. This has been done by examining the jurisdiction in the Native Court, analyses a few decided cases and we highlight the weaknesses of the Native Court. Among weaknesses of the Native Court is, the judges did not refer to the previous precedents when making decisions, the judges are lacking in terms of qualification. They are incompetent because they were mostly old men and they do not possess legal knowledge. Other than that, the system of native courts is unorganized. Under the previous laws, there are procedures laid down in the Native Court Ordinance 1953, but the judges tended to ignore them and use their own way in deciding cases. Furthermore, they use their own personal opinion and thus it creates injustice especially to the innocent party to the disputes. To encounter all these weaknesses, in this research, we also provide the solutions that can be done in order to strengthen the integrity of the Native Court.